Pengenalan Botani sebagai Upaya Peningkatan Literasi Sains Siswa Kelas X SMA pada Materi Keanekaragaman Hayati: indonesia - Surya Ramdani; Syadila Ariesta; Vivi Maulida Cahyani; Rubiyatna Sakaroni (Universitas Mataram, 2026)
The low level of students’ scientific literacy, particularly in understanding biodiversity concepts and conservation efforts, remains one of the challenges in biology learning at the secondary school level. Learning activities that are predominantly theoretical and do not optimally utilize the surrounding environment as a learning resource result in students’ limited contextual understanding and environmental awareness. Therefore, learning activities that connect biological concepts with real-life environmental conditions are needed, one of which is through the introduction of botany. This community service activity aimed to improve the scientific literacy of Grade X students at SMAN 2 Narmada on biodiversity topics through botany-based learning using a contextual learning approach. The activity was conducted in the form of teaching assistance employing the service-learning method, which included the stages of preparation, implementation, and evaluation. The learning implementation utilized interactive teaching materials and the school environment as learning resources. The evaluation was carried out through botany planting activities in the classroom garden as a form of applying the knowledge gained by the students. The results indicated an improvement in students’ understanding of biodiversity concepts, increased student engagement in the learning process, and the development of environmental awareness. Although several challenges were encountered, such as student absenteeism and a lack of focus among some students, overall, the activity was successfully implemented and had a positive impact on biology learning. This botany introduction activity has the potential to be developed as a sustainable learning strategy to enhance students’ scientific literacy.